Peptide-assembled nanoparticles targeting tumor cells and tumor microenvironment for cancer therapy - Zhang, Meichen; Xu, Haiyan (Frontiers in Chemistry, 2023)
Tumor cells and corrupt stromal cells in the tumor microenvironment usually overexpress cancer-specific markers that are absent or barely detectable in normal cells, providing available targets for inhibiting the occurrence and development of cancers. It is noticeable that therapeutic peptides are emerging in cancer therapies and playing more and more important roles. Moreover, the peptides can be self-assembled and/or incorporated with polymeric molecules to form nanoparticles via non-covalent bond, which have presented appealing as well as enhanced capacities of recognizing targeted cells, responding to microenvironments, mediating internalization, and achieving therapeutic effects. In this review, we will introduce the peptide-based nanoparticles and their application advances in targeting tumor cells and stromal cells, including suppressive immune cells, fibrosis-related cells, and angiogenic vascular cells, for cancer therapy.